2022
DOI: 10.1186/s12885-022-09265-1
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic and predictive value of ESR1 fusion gene transcripts in primary breast cancer

Abstract: Background In breast cancer (BC), recurrent fusion genes of estrogen receptor alpha (ESR1) and AKAP12, ARMT1 and CCDC170 have been reported. In these gene fusions the ligand binding domain of ESR1 has been replaced by the transactivation domain of the fusion partner constitutively activating the receptor. As a result, these gene fusions can drive tumor growth hormone independently as been shown in preclinical models, but the clinical value of these fusions have not been reported. Here, we studi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…When first described, ESR1-e2>CCDC170 in ER+ breast cancer cells led to enhanced growth and reduced sensitivity to tamoxifen ( 75 ) suggesting a role for ESR1-e2>CCDC170 in ET resistance. Additional pre-clinical studies ( 74 , 75 , 79 ) showed that the expression of ESR1-e2>CCDC170 fusions in ER-positive breast cancer cells resulted in increased cell migration, increased colony formation, and increased cell proliferation as evidenced by the increase in the number of cells in S-G2/M phase. Li and colleagues ( 74 ) provided detailed evidence supporting the function of ESR1-e2>CCDC170 in promoting breast cancer cell survival and endocrine resistance both in vitro and in xenograft models.…”
Section: Activating Esr1 Fusion Proteins Drive Endocrine Resistance A...mentioning
confidence: 99%
See 1 more Smart Citation
“…When first described, ESR1-e2>CCDC170 in ER+ breast cancer cells led to enhanced growth and reduced sensitivity to tamoxifen ( 75 ) suggesting a role for ESR1-e2>CCDC170 in ET resistance. Additional pre-clinical studies ( 74 , 75 , 79 ) showed that the expression of ESR1-e2>CCDC170 fusions in ER-positive breast cancer cells resulted in increased cell migration, increased colony formation, and increased cell proliferation as evidenced by the increase in the number of cells in S-G2/M phase. Li and colleagues ( 74 ) provided detailed evidence supporting the function of ESR1-e2>CCDC170 in promoting breast cancer cell survival and endocrine resistance both in vitro and in xenograft models.…”
Section: Activating Esr1 Fusion Proteins Drive Endocrine Resistance A...mentioning
confidence: 99%
“…These include fusion proteins associated with ER such as ESR1-CCDC170 ( 73 75 ), and ESR1-YAP1 ( 76 ) and non ER related fusions such as CTNNBL1-RAF1, ACTL6A-PIK3CA, S6KCI-AKT3 ( 71 ), SEC16A-NOTCH1 ( 77 ), SEC22B-NOTCH2 ( 72 ), and ETV6-NTRK3 ( 78 ). A number of these fusions promote tumor growth, and patients expressing these fusion proteins have more rapid disease progression and shorter survival than fusion-negative patients ( 70 , 71 , 75 , 79 ). Identifying the full spectrum of the ESR1 gene fusions and characterizing their role in intrinsic ET resistance is critical for developing novel and effective targeted therapies.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 The most prevalent fusions are between ESR1 and the adjacent gene CCDC170 , comprising over half of ESR1-FUS cases; the remaining fusions involve assorted gene partners. 6 , 8 , 10 , 12 , 13 Analysis of HR+ MBC samples has identified ESR1-FUS at 3-5% prevalence. 14 , 15 These sample sizes are small, and it is unknown how ESR1-FUS prevalence differs in treated versus treatment-naïve conditions.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
“…Other studies suggest higher prevalence limits (up to 22-28%), although likely with higher false-positive rates. 12 , 13 Of note, some immortalized breast cancer lines also carry ESR1 :: CCDC170 fusions, including MCF7, HCC1428, and ZR75-1. 6 , 8 , 12 In summary, ESR1-FUS may be present in at least 1-10% of primary HR+ breast cancer, typically in luminal B tumors, and the most common are ESR1 :: CCDC170 fusions.…”
Section: Molecular Tumor Boardmentioning
confidence: 99%
See 1 more Smart Citation